Loading forces in shallow water running at two levels of immersion - Haupenthal A.* (2010)
Objective: To analyse the vertical and anteroposterior components of the ground reaction force during shallow water running at 2 levels of immersion. Subjects: Twenty-two healthy adults with no gait disorders, who were familiar with aquatic exercises. Methods: Subjects performed 6 trials of water running at a self-selected speed in chest and hip immersion. Force data were collected through an underwater force plate and running speed was measured with a photocell timing light system. Analysis of covariance was used for data analysis. Results: Vertical forces corresponded to 0.80 and 0.98 times the subject's body weight at the chest and hip level, respectively. Anteroposterior forces corresponded to 0.26 and 0.31 times the subject's body weight at the chest and hip level, respectively. As the water level decreased the subjects ran faster. No significant differences were found for the force values between the immersions, probably due to variability in speed, which was self-selected. Conclusion: When thinking about load values in water running professionals should consider not only the immersion level, but also the speed, as it can affect the force components, mainly the anteroposterior one. Quantitative data on this subject could help professionals to conduct safer aquatic rehabilitation and physical conditioning protocols. © 2010 Foundation of Rehabilitation Information.